Penerapan Internal Control Atas Persediaan Pada CV Wijaya Tata Mandiri (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Ari Ahmad, 2018. Internal Control Implementation of Inventory at CV Wijaya Tata Mandiri (under the supervision of Mrs. Prof. Dr. Hj. Sri Mintarti, M.Si as supervisor I and Mr. Muhammad Abadan Syakura, SE, M.SA., Ak as supervisor II)The purpose of this research is to find out and analyze the internal control system of merchandise inventory that is applied to CV Wijaya Tata Mandiri. The type of research used in this study is a type of qualitative research using comparative descriptive research methods. Techniques in data collection were carried out by means of interviews and questionnaires, using an internal control questionnaires analysis tool on elements of internal control consisting of: 1) Control Environment, 2) Risk Assessment, 3) Control Activities, 4) Information and Communication, and 5) Monitoring. From the results of the research, the internal control system in the procedures for managing merchandise inventories applied by CV Wijaya Tata Mandiri was sufficient. However, there are still some that are not in accordance with the elements of internal control according to the theory where there are several duplicate tasks in running the organization and some documents are not authorized with the appropriate parties and there is no written guidelines in writing. Keywords: Internal Control System, Inventory.